Dynamics of charity and reciprocity in the Book of Sirach - Long, Stephen Arden (Forschungen zum Alten Testament, 2023)
Cover -- Title -- Acknowledgments -- Table of Contents -- List of Abbreviations -- Chapter 1: Introduction -- 1.1 Introduction and Status Quaestionis -- 1.2 Historical, Social, and Sectarian Setting of Ben Sira -- 1.2.1 Date of Composition for Sirach -- 1.2.2 Historical Setting -- 1.2.3 Ben Sira's Social Location -- 1.2.4 Sectarian Setting -- 1.2.5 Ben Sira and "Hellenism" -- 1.3 Reciprocity in the Ancient World -- 1.3.1 Introduction: "The Gift" since Mauss -- 1.3.2 Greco-Roman Reciprocity -- 1.3.3 Reciprocity in Biblical and Cognate Literature -- 1.3.4 Can We Use Greco-Roman Comparanda with Ben Sira? -- 1.4 The Text of Sirach -- 1.5 Outline of the Present Work -- 1.6 Supplementary Materials: Text-Criticism of Sir 22:23-26 -- 1.6.1 Text of Sirach 22:23-26 (LXX) -- 1.6.2 Textual Notes -- 1.6.3 Translation of Sir 22:23-26 -- Chapter 2: Generosity and Reciprocity in the Good Life according to Sirach 14:3-19 -- 2.1 Introduction to Sirach 14:3-19 -- 2.2 Text of Sirach 14:3-19 according to Manuscript A -- 2.3 Textual Notes on Sir 14:3-19 -- 2.4 Translation of Sir 14:3-19 -- 2.5 Commentary: Generosity and Return in the Good Life -- 2.6 Generosity, "Benefits," and Friendship in Broader Context -- 2.6.1 Reciprocity among "Friends" in the Hebrew Bible -- 2.6.2 Reciprocity among "Friends" in Hellenistic Friendship -- 2.7 Chapter Conclusion -- 2.8 Supplementary Materials: Text-Criticism of Sir 31:23-24 -- 2.8.1 Text of Sir 31:23-24 according to Manuscript B -- 2.8.2 Textual Notes -- 2.8.3 Translation of Sir 31:23-24 -- 2.8.4 Commentary -- Chapter 3: Decorum in Generosity according to Sirach 18:15-18 and 20:9-17 -- 3.1 Sirach 18:15-18 -- 3.1.1 Introduction to Sirach 18:15-18 -- 3.1.2 Text of Sirach 18:15-18 according to LXX -- 3.1.3 Textual Notes on Sir 18:15-18 -- 3.1.4 Translation of Sir 18:15-18.